Teaching triage in disaster medicine – same subject, but different approach - Khorram-Manesh, Amir (Scandinavian journal of trauma, resuscitation and emergency medicine, 2025)
Disaster management is an inter-, intra-, and cross-disciplinary task in which different specialties partake. Triage is a crucial part of disaster education. A synchronized approach and mutual understanding of triaging and agreement on priorities are essential for saving lives. Educational initiatives in disaster medicine aim to address issues that highlight the differences between more routine multi-casualty incidents and rarer mass casualty incidents. These differences are characterized by the number of victims, available resources, and environmental factors that may jeopardize the safety of victims and healthcare providers. While routine triage algorithms are often used in multiple casualty emergencies, considering environmental factors in mass casualty incidents caused by natural or human-made hazards should be equally important. The impacts of environmental factors are usually not discussed in disaster medicine education, resulting in professionals having difficulties understanding the limitations of implementing routine triage algorithms during disaster response.